(untitled) (Annals of Medical Research, 2023)
Aim: Upper eyelid blepharoplasty (ULB) is a prevalent aesthetic and functional surgery. This study aims to compare the post-operative dry eye syndrome (DES) symptoms and related diagnostic tests between the patients who underwent ULB with or without fat excision. Materials and Methods: A total of 44 patients (22 with fat excision, 22 without) were evaluated preoperatively and post-operatively in the 1st and 6th months for DES parameters (Schirmer I, tear break-up time, and corneal staining score) and Ocular Surface Disease Index (OSDI) score. Results: Patients undergoing ULB regardless of fat excision demonstrated favorable outcomes in both objective DES tests and subjective DES scale in the postoperative 6th month. There was no significant difference between the two surgical groups in terms of DES parameters in both the 1st and 6th months. Conclusions: ULB appears to ameliorate both objective and subjective manifestations of DES. The inclusion of fat excision during the procedure does not seem to exert a significant effect on these outcomes.